Formation and properties of self-consistent Malmberg-Penning trap - Azarenkov, N.A.; Bizyukov, A.A.; Lapshin, V.I.; Maslov, V.I.; Onishchenko, I.N.; Tarasov, I.K.; Tarasov, M.I.; Volkov, E.D. (Вопросы атомной науки и техники, 2005)
In recent years a big attention is given to coherent structures at an explanation of phenomena of the fast convective carry from the scratch-off-layer in devices such as “tokamak” and “stellarator”. Coherent structures can appear at occurrence of the self-consistent electromagnetic traps (similar to Malmberg-Penning trap) with confinement and cooling of charged plasma in them. In this paper the results of researches of an opportunity of the self-consistent confinement configuration formation in the non-neutral plasma represented.